2011
DOI: 10.1074/jbc.m111.241265
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Genetics, Function, and Kinetic Mechanism of TagE, the Wall Teichoic Acid Glycosyltransferase in Bacillus subtilis 168

Abstract: The biosynthetic enzymes involved in wall teichoic acid biogenesis in Gram-positive bacteria have been the subject of renewed investigation in recent years with the benefit of modern tools of biochemistry and genetics. Nevertheless, there have been only limited investigations into the enzymes that glycosylate wall teichoic acid. Decades-old experiments in the model Gram-positive bacterium, Bacillus subtilis 168, using phage-resistant mutants implicated tagE (also called gtaA and rodD) as the gene coding for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 30 publications
1
62
0
Order By: Relevance
“…In addition, no significant differences in expression or localization of LytF were observed in the tagE null mutant strain (Fig. 1b, 3f-g), which has a defect in glycosylation of the major WTA (Allison et al, 2011;Lazarevic et al, 2002). A previous report has demonstrated that TagE is only able to use a poly(GroP) polymer as a substrate (Allison et al, 2011).…”
Section: Expression and Localization Of Lytf In Mutants Of The Lta Symentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, no significant differences in expression or localization of LytF were observed in the tagE null mutant strain (Fig. 1b, 3f-g), which has a defect in glycosylation of the major WTA (Allison et al, 2011;Lazarevic et al, 2002). A previous report has demonstrated that TagE is only able to use a poly(GroP) polymer as a substrate (Allison et al, 2011).…”
Section: Expression and Localization Of Lytf In Mutants Of The Lta Symentioning
confidence: 95%
“…1b, 3f-g), which has a defect in glycosylation of the major WTA (Allison et al, 2011;Lazarevic et al, 2002). A previous report has demonstrated that TagE is only able to use a poly(GroP) polymer as a substrate (Allison et al, 2011). Therefore, it is thought that WTA polymer synthesis is initiated by TagF prior to glycosylation.…”
Section: Expression and Localization Of Lytf In Mutants Of The Lta Symentioning
confidence: 99%
“…The physiological function of this modification is yet unknown (Allison et al, 2011). Together with lipoteichoic acids, WTA accounts for over 60% of the mass of the Gram-positive cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…This cassette was obtained by PCR on genomic DNA (Supplementary Table S1) of a previously constructed tagE::spec strain (Allison et al, 2011) (gift of professor Eric Brown).…”
Section: Mediamentioning
confidence: 99%
“…Decades ago it was shown that glucosylated WTA were required for phage adsorption in B. subtilis 168 (Young, 1967) (Table 1) and the TagE protein (also called GtaA and RodD) of B. subtilis 168 was proposed as the WTA glucosyltransferase based on the indirect genetic evidence (Honeyman and Stewart, 1989;Mauel et al, 1989). Recently, TagE was characterized and demonstrated to be a GroP WTA ␣-glucosyl transferase (Allison et al, 2011). Thus, WTA glycosylation in B. subtilis and S. aureus share similar functions such as phage adsorption and infection.…”
Section: Role Of Wta Glycosylation In Other Gram-positive Bacteriamentioning
confidence: 99%